Development Of Training Programs To Enhance Teachers' Digital Skills With Technological Pedagogical Content Knowledge (TPACK) - Herlina Ike Oktaviani; Deka Dyah Utami (Journal of Educational Technology Studies and Applied Research, 2024)
The development of digital skills for teachers is important in the digital era, especially in the effective integration of technology into teaching and learning. This research focuses on the development of a training program based on Technological Pedagogical Content Knowledge (TPACK) to enhance teachers' ability to utilize educational technology. The program was developed using the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation, to create relevant and adaptive training experiences. The program focuses on a development process designed to meet the diverse needs of participants and address barriers to digital training implementation in various educational contexts. The training results show that the majority of participants successfully mastered the basic TPACK competencies and demonstrated high levels of satisfaction. The program also adapts its approach based on the characteristics and needs of participants at each educational level, incorporating both online and face-to-face sessions. Despite challenges in infrastructure and accessibility, the program has been proven to significantly enhance teachers' digital skills, as evidenced by good graduation rates and positive participant perceptions of the training benefits. Therefore, this TPACK-based training can serve as an effective model in teacher professional development.